Urethral Foreign Body Management: A Case Report. (2004) - Chang, Andy Y.; Koh, Chester J.; Stein, John P.
Abstract : The management of urethral foreign bodies may require the use of various surgical techniques in a urologist's armamentarium. We report a unique case of a urethral foreign body requiring percutaneous and endoscopic techniques for removal.